2021
DOI: 10.1186/s13046-021-01888-9
|View full text |Cite
|
Sign up to set email alerts
|

FGF19/FGFR4 signaling axis confines and switches the role of melatonin in head and neck cancer metastasis

Abstract: Background There is no consensus about the effective dosages of melatonin in cancer management, thus, it is imperative to fully understand the dose-dependent responsiveness of cancer cells to melatonin and the underlying mechanisms. Methods Head and neck squamous cell carcinoma (HNSCC) cells with or without melatonin treatment were used as a research platform. Gene depletion was achieved by short hairpin RNA, small interfering RNA, and CRISPR/Cas9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…All cell lines were cultured in DMEM medium containing 10% fetal bovine serum at 37 °C in a humidified incubator with 5% CO 2 . Western blotting, plasmid transfection, lentiviral infection, cell proliferation, and colony formation assays were carried out as we previously described [ 7 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…All cell lines were cultured in DMEM medium containing 10% fetal bovine serum at 37 °C in a humidified incubator with 5% CO 2 . Western blotting, plasmid transfection, lentiviral infection, cell proliferation, and colony formation assays were carried out as we previously described [ 7 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies revealed melatonin has significant inhibitory effects on numerous cancers [5][6][7][8][9]. Melatonin exerted anticancer actions in almost every stage of tumor generation and development through the joint effect of multiple functions, such as inhibiting proliferation, angiogenesis and metastasis, affecting aerobic metabolism, and enhancing chemotherapy efficiency [5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, a hormone mainly secreted from the pineal gland, has been proven to possess extensive biological activities including circadian rhythms regulation, anti-oxidation, anti-inflammation and immunoregulation [1][2][3][4][5]. As to cancer, mounting evidence indicates that melatonin exhibits oncostatic features at the initiation, progression and metastasis phases through multiple and interrelated mechanisms [5][6][7][8][9][10][11]. Esophageal squamous cell carcinoma (ESCC) is ranked as the 6th leading cause of cancer-related deaths in the world [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed as previously described ( 21 ). Briefly, paraffin-embedded xenografts or tissues were cut into 3-μm sections and mounted on slides, subjected to antigen retrieval in hot citrate buffer (pH = 7.4), then blocked in 10% normal goat serum.…”
Section: Methodsmentioning
confidence: 99%